Implementation of a Trilingual Talent Development Program to Enhance Communication Skills in Madrasah Ibtidaiyah - Faudina Husna Afifah; Ali Mahsun (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2023)
Each madrasah has its own strategy for developing students’ communication talents through specialized guidance programs. This study aims to describe the implementation of the Three-Language Talent Guidance Program (PBB) in improving students’ communication skills at MI Darussalam Badang Ngoro Jombang. The research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing or verification. Data validity was ensured by prolonged observation, source triangulation, technique triangulation, and the use of reference materials. The findings indicate that the program covers three languages—Indonesian, English, and Arabic—designed to enhance students’ ability to communicate effectively and appropriately. The program is specifically implemented for Arrohman class students and is carried out in groups with the collaboration of the program coordinator, teachers, and parents. The implementation of the program has significantly improved students’ speaking skills, self-confidence, and public speaking abilities, enabling them to participate in and achieve awards in various speech competitions.